PERILAKU MEROKOK DITINJAU DARI PENGARUH KELOMPOK TEMAN SEBAYA DAN POLA ASUH PERMISIF PADA REMAJA DI DESA KINCANG WETAN - Wicaksono, David Ary (Widya Warta, 2015)
This study is intended to examine the  influence of peer group and permissive parenting pattern toward smoking behaviour. The subject of the research is  60 teenagers of Kincang Wetan village. The scale of smoking behavior was applied as a measuring tool. The data collecting employed random sampling technique. The data were analyzed using  two-predictor-regression analysis method with SPSS version 18.  The data analysis conveyed the correlation coefficient R = 0.983, F regression = 797.488; p = 0.000 (p <0.05). It proved that peer group and permissive parenting pattern influenced smoking behaviour. Consequently,  the variables peer group and permissive parenting pattern can be used as a predictor for  the smoking behavior of teenagers.